Sensitivity Test of Pedada (Sonneratia alba) Leaf Extract Against the Growth of Staphylococcus aureus, Escherichia coli, and Aeromonas hydrophila Bacteria - Wiya, Siti Ada; Wahyuni, Sri; Mursawal, Asri; Nursyirwani, Nursyirwani (Journal of Coastal and Ocean Sciences, 2025)
Sonneratia alba (Pedada) is one of the potential mangroves as a natural antibacterial because it contains secondary metabolites, such as flavonoids, saponins, steroids, tannins, and terpenoids. This study aimed to determine the inhibitory power of Pedada leaf extract in inhibiting the growth of Staphylococcus aureus, Escherichia coli, and Aeromonas hydrophila. The research method used is experimental, including sample preparation, extraction, and sensitivity tests using the Kirby-Bauer disc method. This study used 100%, 50%, 25%, and 12.5% extract doses, positive control (Oxytetracycline), and negative control (a quade). The results showed that Pedada leaf extract could inhibit the growth of pathogenic bacteria; 100% concentration was the concentration with the widest inhibition zone diameter of S. aureus 15.48 mm, E. coli 13.37 mm, and A. hydrophila 13.88 mm. Based on this study's results, the best extract concentration for inhibiting bacterial growth is 100% concentration